Use of cognitive task analysis to guide the development of performance-based assessments for intraoperative decision making. - Pugh, Carla M; Darosa, Debra A (Military Medicine)
Background: There is a paucity of performance-based assessments that focus on intraoperative decision making. The purpose of this article is to review the performance outcomes and usefulness of two performance-based assessments that were developed using cognitive task analysis (CTA) frameworks.Methods: Assessment-A used CTA to create a "think aloud" oral examination that was administered while junior residents (PGY 1-2's, N = 69) performed a porcine-based laparoscopic cholecystectomy. Assessment-B used CTA to create a simulation-based, formative assessment of senior residents' (PGY 4-5's, N = 29) decision making during a laparoscopic ventral hernia repair. In addition to survey-based assessments of usefulness, a multiconstruct evaluation was performed using eight variables.Results: When comparing performance outcomes, both approaches revealed major deficiencies in residents' intraoperative decision-making skills. Multiconstruct evaluation of the two CTA approaches revealed assessment method advantages for five of the eight evaluation areas: (1) Cognitive Complexity, (2) Content Quality, (3) Content Coverage, (4) Meaningfulness, and (5) Transfer and Generalizability.Conclusions: The two CTA performance assessments were useful in identifying significant training needs. While there are pros and cons to each approach, the results serve as a useful blueprint for program directors seeking to develop performance-based assessments for intraoperative decision making.